THE INSERTION OF THE RESIDENT IN NURSING IN A SURGICAL CARE UNIT: PRACTICES AND CHALLENGES - Livia Crespo Drago; Roberta Luiza Salum; Selma Regina Andrade; Michele Medeiros; Monique Mendes Marinho (Universidade Federal do Paraná, 2013)
The inclusion of nursing residents can promote changes in the care environment in the hospital ambit. This research aimed to understand whether changes took place or not in the nursing practices, as a result of the insertion of residents of this category in an inpatient unit in a University Hospital, in the perception of the nursing team. This research is exploratory-descriptive, has a qualitative approach, and uses the Bardin analysis technique, from which two categories resulted: The perspective of the nurse technicians and The perspective of the nurses. The participants did not perceive substantive changes in the practices resulting from the insertion of the nursing residents. Intermediate situations were identified, which were understood as challenges to the Program. The improvement of modes of insertion of the resident in the practice settings could contribute to education in nursing, to the process of continuing education in health, and to the care given in the institutions to society.